The Influence of Interest, Motivation, and Creativity on Household Industry Income in Bireuen - Saprida Bachtiar; M. Rasyidin; Asrida Asrida (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the influence of interest, motivation, and creativity on the income of household industries in Bireuen Regency. Household industries play a strategic role in supporting the regional economy; however, they still face various challenges that affect the income levels of business owners. This research employs a quantitative approach using multiple linear regression analysis to examine the relationships between these variables. Data were collected through questionnaires distributed to household industry entrepreneurs in Bireuen Regency and analyzed using classical assumption tests and hypothesis testing. The findings reveal that entrepreneurial interest does not significantly impact household industry income, indicating that a strong desire to run a business does not necessarily translate into higher earnings without the support of other factors such as access to capital and effective business strategies. Similarly, motivation does not make a significant contribution to income growth, even though it may enhance productivity. Additionally, creativity in running a business does not have a notable effect on income, possibly due to the lack of effective marketing strategies or limited market access. On the other hand, external factors such as government policies, infrastructure support, and access to financial resources play a more dominant role in determining household industry income levels.